Reinterpretation of the Advocate Code of Ethics in Facing the Digitalization of Legal Practice - Angelia Frisca; Intan Agustin; Ema Agustin; Bagus Wahyu; Ahmad Hasan; M. Afiq Safana; Syifa Rana Tsary (Jurnal Ilmiah Multidisiplin, 2026)
The development of information technology has driven fundamental transformations in legal practice and the working patterns of the legal profession. The digitalization of the judiciary through e-Court, the use of social media, and online legal communication have reshaped the way advocates deliver legal services. These developments enhance efficiency and access to justice; however, they also generate new ethical challenges that may undermine the integrity and professionalism of advocates. The Indonesian Advocates’ Code of Ethics, as a normative instrument, is required to remain relevant to the evolving dynamics of digital legal practice. This study examines the relevance of ethical regulations in responding to digital legal practices and the need for their reinterpretation to preserve the dignity of the legal profession. The research employs a normative legal method with statutory and conceptual approaches. The findings indicate that conventionally oriented ethical regulations have not fully addressed ethical issues arising in digital spaces, particularly concerning social media, online publications, and the use of artificial intelligence. Therefore, a reinterpretation of the code of ethics that is adaptive to technological developments is necessary, without abandoning the values of officium nobile, in order to strengthen public trust in the legal profession.